Lean in, but keep your balance - Vinnicombe, Susan (Cranfield University School of Management, 2013)
Sheryl Sandberg has an enviable pedigree. She is Chief Operating Officer at Facebook and is ranked on Fortune’s list of the 50 Most Powerful Women in Business. She has strong views on why so few women make it to the top but is she right?